Enhancement of critical current density in Mg incorporated ex-situ MgB2 via co-addition of B4C and Dy2O3 - Peh, Hoo Keong; Chen, Soo Kien; Hapipi, Nurhidayah Mohd; Kechik, Mohd Mustafa Awang; Lim, Kean Pah; Tan, Kar Ban; Shaari, Abdul Halim; Shabdin, Muhd Kashfi; Mohamed, Arebat Ryad Alhadei; Lee, Oon Jew; Huy, Nguyen Quang; Tran, Duc H.; et al. (Elsevier Ltd, 2025)
By utilising the solid-state sintering route, bulk polycrystalline ex-situ MgB2 added with 0.5 mol Mg + 5.0 wt% B4C + x wt% Dy2O3 (x = 0.0, 0.5, 1.0, 2.0) were fabricated. X-ray Diffraction (XRD) showed the dominance of MgB2 phase across the samples. Simultaneous addition of Mg, B4C and Dy2O3 was found to increase the MgB2 fraction. The onset of critical temperature remained unchanged indicating negligibly small C doping into the MgB2. The critical current density, Jc was measured using a SQUID magnetometer on rectangular bulk samples. As compared with the pure ex-situ MgB2, Jc of the sample for x = 2.0 is around 30 times larger reaching 1.2 × 105 A·cm−2 at 20 K and self-field. As revealed by the transmission electron microscopy images, the presence of DyB4 nanoparticles may serve as effective flux pinning centres leading to the great enhancement of Jc.